2022
DOI: 10.1039/d2ta03647a
|View full text |Cite
|
Sign up to set email alerts
|

Rationally regulating the terminal unit and copolymerization spacer of polymerized small-molecule acceptors for all-polymer solar cells with high open-circuit voltage over 1.10 V

Abstract: Two polymerized small molecule acceptors with wide bandgaps of ∼1.65 eV and high-lying LUMO energy levels above −3.70 eV were designed by introducing a novel terminal unit. Efficient all-PSCs with high VOC over 1.10 V were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This is presumably because similar to other PSMAs, thiophene linker weakens the electron-accepting ability of adjacent IDO units and meanwhile conformation torsion impedes the electron delocalization on the entire conjugated mainchain. 37 Besides, the molar absorption coefficients of these polymers are in the range of 0.84–1.23 10 5 M −1 cm −1 , which is close to that of normal PSMAs. 43 In the solid state, these polymers display similar absorption profiles to that in solution, implying the inconspicuous interchain aggregation effect.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This is presumably because similar to other PSMAs, thiophene linker weakens the electron-accepting ability of adjacent IDO units and meanwhile conformation torsion impedes the electron delocalization on the entire conjugated mainchain. 37 Besides, the molar absorption coefficients of these polymers are in the range of 0.84–1.23 10 5 M −1 cm −1 , which is close to that of normal PSMAs. 43 In the solid state, these polymers display similar absorption profiles to that in solution, implying the inconspicuous interchain aggregation effect.…”
Section: Resultssupporting
confidence: 58%
“…on the benzene ring is required to lower the motif's lowest unoccupied molecular orbital (LUMO) energy levels due to the relatively weak electron-accepting capability when served to construct acceptor polymers. 37 Alternatively, transforming the IDO unit into a bifunctional indacene-1,3,5,7-tetraone (ITO) unit using a fusion strategy is expected to be an effective method. In 2014, Würthner et al found that ITO-based small molecules show lower-lying LUMO energy levels than reference molecules with IDO units, and they also pointed out that in such polymers, the LUMO should be much more delocalized than the HOMO, which might lead to n-type semiconducting polymer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the solar cell based on PM6:BTP-2F-ThCl can achieve an efficiency of 17.70%, also outperforming the counterparts. At last, a 17.14% PCE is gained here due to the better HTM layer, which is one of the best values for non-halogenated solvent-treated binary all-polymer solar cells. …”
Section: Resultsmentioning
confidence: 92%
“…In order to obtain a high V oc in binary OSCs, some factors have been investigated, such as energy level matching and energy loss in the donor (D) and acceptor (A), interfacial contact of D and A, morphology regulation, charge transfer state, carrier density and molecular packing behavior in the active layer, temperature and light intensity of the device, [7][8][9][10][11][12] as shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%